Agroindústria de leite como estratégia de desenvolvimento rural sustentável para a agricultura familiar de Campo Bonito e Guaraniaçu, Paraná - Brasil - Meneghatti, Marcelo Roger (2014)
The purpose of this paper was to identify the main actions to be taken into account for the implementation of a dairy plant in Campo Bonito Municipality in the Western region of Paraná-Brazil, which already has a partially implemented physical structure. The agricultural past of Brazil is often characterized by constant reduction in the income of the family farmer, which, in most cases, is a reason for many families leave the rural areas and visualize in the urban centers an attempt to improve the quality of life. On the other hand, what we have is an increase in demand for agricultural, colonial or organic origin products since these are considered natural or ecological and less harmful to health than industrial products on a large scale. Therefore this is indeed a good opportunity for farmers to enhance their capacity to generate income, adding value to their traditional processed products. In the west region of Paraná, the dairy products stand out due to its significant dairy cattle that this region presents. The municipality of Campo Bonito - PR has a project conceived by milk producers of two cooperatives, with the aim of milk processing and adding value, but not yet in operation. This little project was started by the farmers´ will initially intended to market in association their fresh milk, on a small scale, then, they began to invest in the idea of processing and adding value to their product, in the form of derivatives. This business project will guarantee the income of families in rural areas involved in this activity. For achieving the objective of this paper was necessary to carry out the description of the historical context of the enterprise and the observation of the processes involved in the entire production chain. For that, dialogued interviews with the dairy farmers of the region and who are involved in the project were carried out, in order to raise the real difficulties of these families and demonstrate how entrepreneurship can be useful for this context. Based on this knowledge, it was performed a Business Plan to reach the possible viability of this small production unit. The paper concluded that there is viability in the project, and that it can benefit the involved families and contribute to sustainability in family farming, thus meeting the social needs of this region, however, with exceptions in some actions that must be performed by the business project creators, especially in the management of the enterprise that needs to be done in the best possible way and with a high level of professionalism for fulfilling the goals and the achievement of the objectives proposed by the business project